Contemporary Gynecologic Practice - Darwish, Atef (IntechOpen, 2015)
Gynecology is frequently changing due to extensive implementation of high technology in both, the diagnosis and management of gynecologic problems. General gynecologists, gynecologic endocrinologists, infertility specialists, gynecologic endoscopists, and gynecologic oncologists will find attractive, new information in this book.